CGIAR Climate Impact Platform establishes 600 member strong global Climate Community of Practice across all 15 research centers to enhance collaboration and expertise - Edward-Uwadiale, Regina; Smith, Georgina (CGIAR System Organization, 2024)
For the first time ever, a climate community of practice was launched in 2023 across all CGIAR centers to strengthened capacity among around 600 people.